Dietary restriction increases protective gut bacteria to rescue lethal methotrexate-induced intestinal toxicity. Issue 1 (9th November 2020) - Tang, Duozhuang; Zeng, Ting; Wang, Yiting; Cui, Hui; Wu, Jianying; Zou, Bing; Tao, Zhendong; Zhang, Liu; Garside, George B.; Tao, Si
ABSTRACT: Methotrexate (MTX) is a typical chemotherapeutic drug that is widely used in the treatment of various malignant diseases as well as autoimmune diseases, with gastrointestinal toxicity being its most prominent complication which could have a significant effect on the prognosis of patients. Yet effective ways to alleviate such complications remains to be explored. Here we show that 30% dietary restriction (DR) for 2 weeks dramatically increased the survival rate of 2-month-old female mice after lethal-dose MTX exposure. DR significantly reduced intestinal inflammation, preserved the number of basal crypt PCNA-positive cells, and protected the function of intestinal stem cells (ISCs) after MTX treatment. Furthermore, ablating intestinal microbiota by broad-spectrum antibiotics completely eliminated the protective effect achieved by DR. 16S rRNA gene deep-sequencing analysis revealed that short-term DR significantly increased the Lactobacillus genus, with Lactobacillus rhamnosus GG gavage partially mimicking the rescue effect of DR on the intestines of ad libitum fed mice exposed to lethal-dose MTX. Together, the current study reveals that DR could be a highly effective way to alleviate the lethal injury in the intestine after high-dose MTX treatment, which is functionally mediated by increasing the protective intestinal microbiota taxa in mice. Keywords: Dietary restriction, Methotrexate, Gut microbiota, Intestinal stem cells, intestinal toxicity